Exploring Sustainability Reports in The Indonesian Palm Oil Industry - Nurhayati Soleha; Rita Rosiana (PT. EQUATOR SINAR AKADEMIA, 2021)
The purpose of this study is to assess the quality and maturity of sustainability reports of palm oil companies listed on the Indonesia Stock Exchange (IDX). The findings indicate that there are few differences in the maturity levels of palm oil companies in implementing sustainability reporting based on GRI standards and the maturity sustainability reporting at a moderate level of relevant information. The majority of disclosure of sustainability reports is general disclosures and less present in economic and environmental disclosures. Companies need to improve the quality of their sustainability reporting and strengthen the validity of the measurement. Sustainability reports have the potential to improve the sustainability agenda by allowing management and shareholders to make more informed decisions about sustainability initiatives.